Dual task and postural control in Alzheimer's and Parkinson's disease - Andrade, Larissa Pires De; Rinaldi, Natália Madalena; Coelho, Flávia Gomes De Melo; Tanaka, Kátia; Stella, Florindo; Gobbi, Lilian Teresa Bucken (Universidade Estadual Paulista, 2014)
Patients with neurodegenerative diseases are required to use cognitive resources while maintaining postural control. The aim of this study was to investigate the effects of a frontal cognitive task on postural control in patients with Alzheimer, Parkinson and controls. Thirty-eight participants were instructed to stand upright on a force platform in two experimental conditions: single and dual task. Participants with Parkinson's disease presented an increase in the coefficient of variation greater than 100% in the dual task as compared to the single task for center of pressure (COP) area and COP path. In addition, patients with Parkinson's and Alzheimer's disease had a higher number of errors during the execution of the cognitive task when compared to the group of elderly without neurodegenerative diseases. The motor cortex, which is engaged in postural control, does not seem to compete with frontal brain regions in the performance of the cognitive task. However, patients with Parkinson's and Alzheimer's disease presented worsened performance in cognitive task.

Pacientes con enfermedades neurodegenerativas utilizan de recursos cognitivos para el mantenimiento del control postural. El objetivo de este estudio fue investigar los efectos de una tarea cognitiva frontal en el control postural de pacientes con enfermedad de Alzheimer, enfermedad de Parkinson y ancianos sin enfermedades neurodegenerativas. Treinta y ocho participantes fueron instruidos para mantenerse en pie sobre una plataforma de fuerza en dos condiciones experimentales: tarea simple y doble tarea con una tarea cognitiva frontal. Hubo un aumento en el coeficiente de variación superior a 100% en el área y en la trayectoria del centro de presión (CP) en condiciones de doble tarea en los pacientes con Parkinson. También fue observada diferencia significativa entre los grupos, revelando que los pacientes con Parkinson y Alzheimer tuvieron un número de errores más grande durante la realización de la tarea cognitiva en comparación con el grupo de sujetos sin enfermedades neurodegenerativas. La corteza motora que participa en el mantenimiento del control postural parece no competir con las regiones frontales del cerebro en el rendimiento de este tipo de tarea cognitiva, sin embargo, los pacientes con enfermedad de Parkinson y la enfermedad de Alzheimer presentaron peor rendimiento durante la ejecución de una tarea cognitiva frontal.

Pacientes com doenças neurodegenerativas utilizam recursos cognitivos para manutenção do controle postural. O objetivo deste estudo foi investigar os efeitos de uma tarefa cognitiva frontal no controle postural em pacientes com Alzheimer, com Parkinson e idosos sem doenças neurodegenerativas. Trinta e oito participantes foram instruídos a ficar em pé sobre uma plataforma de força em duas condições experimentais: tarefa simples e tarefa dupla com uma tarefa cognitiva frontal. Foi observado aumento no coeficiente de variação superior a 100% na área e na trajetória do centro de pressão (COP) em condição de tarefa dupla em pacientes com Parkinson. Foi observada também, diferença significativa na comparação entre grupos, mostrando que pacientes com Parkinson e Alzheimer tiveram maior número de erros durante a execução da tarefa cognitiva, quando comparado ao grupo de idosos sem doenças neurodegenerativas. O córtex motor envolvido na manutenção do controle postural parece não competir com regiões frontais cerebrais no desempenho desse tipo de tarefa cognitiva, no entanto, os pacientes com doença de Parkinson e doença de Alzheimer apresentaram pior desempenho durante a execução de uma tarefa cognitiva frontal.
Doble tarea y el control postural en la enfermedad de Alzheimer y la enfermedad de Parkinson
Tarefa dupla e controle da postura na doença de Alzheimer e na doença de Parkinson
Keywords: postural control; dual task; Alzheimer's disease; Parkinson's disease; controle da postura; tarefa dupla; doença de Alzheimer; doença de Parkinson